Current status and pillars of direct air capture technologies - Ozkan, Mihrimah; Nayak, Saswat Priyadarshi; Ruiz, Anthony D.; Jiang, Wenmei (iScience, 2022)
Climate change calls for adaptation of negative emission technologies such as direct air capture (DAC) of carbon dioxide (CO2) to lower the global warming impacts of greenhouse gases. Recently, elevated global interests to the DAC technologies prompted implementation of new tax credits and new policies worldwide that motivated the existing DAC companies and prompted the startup boom. There are presently 19 DAC plants operating worldwide, capturing more than 0.01 Mt CO2/year. DAC active plants capturing in average 10,000 tons of CO2 annually are still in their infancy and are expensive. DAC technologies still need to improve in three areas: 1) Contactor, 2) Sorbent, and 3) Regeneration to drive down the costs. Technology-based economic development in all three areas are required to achieve <$100/ton of CO2 which makes DAC economically viable. Current DAC cost is about 2–6 times higher than the desired cost and depends highly on the source of energy used. In this review, we present the current status of commercial DAC technologies and elucidate the five pillars of technology including capture technologies, their energy demand, final costs, environmental impacts, and political support. We explain processing steps for liquid and solid carbon capture technologies and indicate their specific energy requirements. DAC capital and operational cost based on plant power energy sources, land and water needs of DAC are discussed in detail. At 0.01 Mt CO2/year capture capacity, DAC alone faces a challenge to meet the rates of carbon capture described in the goals of the Paris Agreement with 1.5–2°C of global warming. However, DAC may partially help to offset difficult to avoid annual emissions from concrete (∼8%), transportation (∼24%), iron-steel industry (∼11%), and wildfires (∼0.8%). [Display omitted] Chemical engineering; Energy sustainability; Environmental technology; Mechanical engineering